2015
DOI: 10.3382/ps/pev152
|View full text |Cite
|
Sign up to set email alerts
|

Bitter, sweet and umami taste receptors and downstream signaling effectors: Expression in embryonic and growing chicken gastrointestinal tract

Abstract: Taste perception is a crucial biological mechanism affecting food and water choices and consumption in the animal kingdom. Bitter taste perception is mediated by a G-protein-coupled receptor (GPCR) family-the taste 2 receptors (T2R)-and their downstream proteins, whereas sweet and umami tastes are mediated by the GPCR family -taste 1 receptors (T1R) and their downstream proteins. Taste receptors and their downstream proteins have been identified in extra-gustatory tissues in mammals, such as the lungs and gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Umami taste receptors ( T1R1 and T1R3 ) are expressed in gut enteroendocrine cells and contribute to nutrient sensing, absorption and hormone releasing . In chickens, nutrient‐sensing receptors of T1R1 and T1R3 are mainly responsible for l ‐amino acid sensing, and the solo T1R3 can also serve as a monosaccharide taste sensation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Umami taste receptors ( T1R1 and T1R3 ) are expressed in gut enteroendocrine cells and contribute to nutrient sensing, absorption and hormone releasing . In chickens, nutrient‐sensing receptors of T1R1 and T1R3 are mainly responsible for l ‐amino acid sensing, and the solo T1R3 can also serve as a monosaccharide taste sensation .…”
Section: Discussionmentioning
confidence: 99%
“…Umami taste receptors (T1R1 and T1R3) are expressed in gut enteroendocrine cells and contribute to nutrient sensing, absorption and hormone releasing. 40,41 In chickens, nutrient-sensing receptors of T1R1 and T1R3 are mainly responsible for L-amino acid sensing, and the solo T1R3 can also serve as a monosaccharide taste sensation. 42 The BCAAs, including Val, Leu and Ile as essential amino acids, are involved in several important functions, such as regulation of nutrient metabolism and as neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned receptors share the gustducin G‐protein but follow a transduction pathway triggered by the β and γ G gust subunits. The βγ complex activates the effector PLC Cβ2 (PLCβ2) which in turn converts the membrane lipid phosphatidylinositol 4,5‐bisphosphate (PIP 2 ) into IP 3 and DAG 2 nd messenger molecules . IP 3 in particular can bind to receptors which open intracellular Ca 2+ stores, which in turn propagate the opening of so‐called store‐operated channels .…”
Section: Tastementioning
confidence: 99%
“…Sawamura et al revealed that a chicken fatty acid receptor candidate, GPR120 (G-protein-coupled receptor 120), cloned from chicken oral tissue, responded to fatty acids [14]. With respect to the sense of umami taste in chickens, one of the umami taste receptors, the T1R1/T1R3 heterodimer, was expressed in the oral and gastrointestinal tract tissues in chickens [15] and was activated by L-alanine and L-serine [16]. In another study, we revealed that primary culture cells from isolated taste buds from the chicken palate responded to a mixture of MPG and IMP [17].…”
Section: Introductionmentioning
confidence: 97%